IMPLEMENTASI INOVASI DIGITAL MELALUI WEBSITE DETEKSIANAKSEHAT.COM DALAM MONITORING TUMBUH KEMBANG DAN SDIDTK ANAK USIA DINI DI KB-TK LABSCHOOL UNESA 2 SURABAYA - Qatrunnada Naqiyyah Khusmitha; Vina Firmanty Mustofa; Karunia Wijayanti; Devi Maya Arista; Nidya Comdeca Nurvitriana (Universitas Mataram, 2026)
The golden age is a critical time in a child's development that influences their social, emotional, and intellectual progress. However, there are still challenges in tracking children's growth and development in early childhood education institutions, particularly with the manual recording system and the lack of cooperation with medical professionals. In order to provide the integrated, long-term monitoring of children's growth and development, digital technologies are therefore required. In order to monitor growth and development based on Stimulation, Detection, and Early Intervention of Growth and Development (SDIDTK) at KB-TK Labschool Unesa 2 Surabaya, this community service project intends to use digital innovation through the deteksianaksehat.com website. The activity technique involves identifying problems, setting up facilities, and administering growth and development tests to 35 PG, Kindergarten A, and Kindergarten B pupils utilising e-SDIDTK based on the deteksianaksehat.com website. The activity's outcomes demonstrated improvements in the pace at which children's growth and development were reported, as well as in examination efficiency and recording accuracy. Of the 35 children, 73% displayed development that was age-appropriate, 24% fell into the questionable category, and 3% had deviations that needed more investigation. The digital, effective, and long-lasting early detection of children's growth and development has been strengthened by the deployment of e-SDIDTK via the deteksianaksehat.com website. In order to support the Integrative Holistic Preschool Program, it also improves the digital literacy of preschool teachers and fosters communication between educators, parents, and health professionals.